2022
DOI: 10.1002/elsc.202200029
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the combined effect of surface topography and substrate rigidity in human bone marrow stem cell cultures

Abstract: The combined effect of surface topography and substrate rigidity in stem cell cultures is still under-investigated, especially when biodegradable polymers are used. Herein, we assessed human bone marrow stem cell response on aliphatic polyester substrates as a function of anisotropic grooved topography and rigidity (7 and 12 kPa). Planar tissue culture plastic (TCP, 3 GPa) and aliphatic polyester substrates were used as controls. Cell morphology analysis revealed that grooved substrates caused nuclei orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…[190] With respect to lineage commitment in appropriate media, high substrate rigidity (12 kPa) and surface topography (bidirectional grooves of 1-2 μm dimensionality) have been shown to favor osteogenic and chondrogenic differentiation, while low substrate rigidity (7 kPa) alone or in combination with surface topography (bidirectional grooves of 1-2 μm dimensionality) was shown to promote tenogenic and adipogenic differentiation. [191] This is in alignment with other studies, where stiffness was also considered as a more potent than topography MSC differentiation driving factor [192] and topography was considered more potent than rigidity regulator of cell adhesion, shape, and spreading. [193] It is also Table 3.…”
Section: Stiffness and Topography On Msc Responsesupporting
confidence: 88%
“…[190] With respect to lineage commitment in appropriate media, high substrate rigidity (12 kPa) and surface topography (bidirectional grooves of 1-2 μm dimensionality) have been shown to favor osteogenic and chondrogenic differentiation, while low substrate rigidity (7 kPa) alone or in combination with surface topography (bidirectional grooves of 1-2 μm dimensionality) was shown to promote tenogenic and adipogenic differentiation. [191] This is in alignment with other studies, where stiffness was also considered as a more potent than topography MSC differentiation driving factor [192] and topography was considered more potent than rigidity regulator of cell adhesion, shape, and spreading. [193] It is also Table 3.…”
Section: Stiffness and Topography On Msc Responsesupporting
confidence: 88%
“…Through this mechanism, substrate stiffness influences the ultimate differentiation of mesenchymal stem cells, with cells tending to progress along a lineage that mirrors native tissues with similar mechanical properties (Evans et al, 2009; Guo et al, 2020; Ribeiro et al, 2022; Zigon‐Branc et al, 2019). In particular, mesenchymal stem cells demonstrate greater spreading on stiffer substrates, adopting the flattened, extended morphology of osteoblasts (Xia et al, 2022).…”
Section: Methods Of Mechanical Stimulation For Bone Repairmentioning
confidence: 99%
“…Hydrostatic pressure (HP), fluid shear stress (FSS), compression, and stretching mechanical stimulation work together with the complex structure of ECM to affect cell fate 174 . Therefore, it is believed that researches on the combined effects of multiple physical cues can better simulate the microenvironment in vivo, thus promoting the osteogenic differentiation of cells 175 . Reinwald Y et al confirmed that intermittent hydrostatic pressure (IHP) (270 kPa) in combination with topographical cues (fiber alignment) could direct the fate of MSCs, and enhanced the effect of osteogenesis 174 .…”
Section: Biomaterials-induced Physicomechanical Stimuli Towards Mscsmentioning
confidence: 99%
“…As additional insights into the interaction between cells and ECM in recent years, it was found that the combination of matrix stiffness and nano- topography significantly affected the fate of cells as well 175 . After attaching to the random nanofibers, cells presented apparent stretching morphology and transformed mechanical signals into intracellular signals through cytoskeletal rearrangement, thus promoting osteogenic differentiation 174 .…”
Section: Biomaterials-induced Physicomechanical Stimuli Towards Mscsmentioning
confidence: 99%
See 1 more Smart Citation